Nonlinear vinylidene fluoride copolymers
By using a low-temperature initiator in an aqueous medium to polymerize vinylidene fluoride, functionalized comonomer and fluorinated olefinic comonomer, the branched nonlinear fluorinated copolymer is solved, and the low performance of the binder in the prior art is solved. and the problem of high content improves the adhesion performance and battery capacity of the battery electrode.
Patent Information
- Application Number
- CN202380039128.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-08
- Filing Date
- 2023-05-18
- Publication Date
- 2024-12-20
AI Technical Summary
The prior art is difficult to obtain branched nonlinear structures by copolymerizing vinylidene fluoride with functionalized comonomers, and in battery electrode adhesive applications, there is a problem of high adhesive content and low performance.
The suspension polymerization of vinylidene fluoride, functionalized comonomer and fluorinated olefinic comonomer are used to form a nonlinear fluorinated copolymer containing at least 10% branched structure, using Adhesive to battery electrode.
The efficient preparation of branched nonlinear fluorinated copolymers is achieved, which improves the electrode bonding performance, reduces the binder content, and enhances the battery capacity and active material load.
Smart Images

Figure BDA0005123486280000021 
Figure BDA0005123486280000041 
Figure BDA0005123486280000061
Abstract
Description
Technical Field
[0001] The present invention relates to novel non-linear functionalized vinylidene fluoride copolymers comprising vinylidene fluoride, one or more functionalized comonomers and one or more fluorinated olefinic comonomers, a process for their preparation and their use as battery electrode binders.
[0002] Related Background Technology
[0003] Vinylidene fluoride copolymers are traditionally used in applications requiring special properties, such as low surface energy, high chemical resistance, aging resistance and electrochemical stability. There is a need for fluorinated polymers with modified properties imparted by functional groups, which can improve their properties, especially adhesion to metal foils, especially those used as current collectors in lithium-ion secondary batteries.
[0004] However, due to the aggressiveness of fluorinated polymerized free radicals, it is difficult to add functionalized comonomer units directly to vinylidene fluoride copolymers during polymerization. In one example of a method for producing a functionalized vinylidene fluoride copolymer, a functionalized comonomer (e.g., (meth) acrylic acid) is grafted onto a preformed vinylidene fluoride copolymer chain using methods known in the art. Such materials have been developed to improve adhesion or hydrophilicity to metals (e.g., aluminum or copper) while utilizing the mechanical properties and chemical inertness of poly (vinylidene fluoride) (PVDF) copolymer-based materials. As described in Heng, T. et al., "Graft Modification of PVDF-Based Fluoropolymers", Progress in Chemistry, 33 (4), 2021, 596-609, these materials are generally produced by surface functionalization of preformed PVDF materials to obtain graft copolymers. The disadvantage of such graft copolymers is that grafting is generally limited to surface functionalization. These types of materials are non-uniformly functionalized, their production processes are limited to already formed articles, and the harsh processes used can lead to chain scission, which can compromise the mechanical properties of the final material.
[0005] US8337725 discloses the copolymerization of vinylidene fluoride with at least one hydrophilic (meth) acrylic monomer of the following formula:
[0006]
[0007] Wherein, R1, R2, and R3 are the same or different and are independently a hydrogen atom or a C1-C3 hydrocarbon group, and R OH The method is to produce a linear vinylidene fluoride copolymer product. Although the method produces a linear, functionalized copolymer product, the reaction time is relatively long and the final productivity is low, resulting in increased costs.
[0008] US9434837 discloses an emulsion process in which a comonomer containing an acid group is added to the polymerization process in an amount of up to 1.0 wt. % relative to the total monomers at a temperature of 20-130°C and a pressure of 280-20,000 kPa.
[0009] US9441054 discloses an emulsion polymerization of vinylidene fluoride comprising methacrylic monomers and comprising end groups having the formula -CF2H and / or CH3 in an amount of at least 30 mmoles per kg of vinylidene fluoride (VDF) repeating units.
[0010] US10079388 discloses an aqueous latex comprising at least one vinylidene fluoride polymer produced by emulsion polymerization comprising repeating units derived from vinylidene fluoride and at least one (meth)acrylic monomer.
[0011] WO2018 / 092675 discloses copolymers of vinylidene fluoride, chlorotrifluoroethylene and acrylic acid derivatives. The polymerization reaction time is said to be 100 hours or less, with representative examples showing 32 hours and 19 hours at 28°C.
[0012] WO2018092677 (US2019 / 0326602) discloses an electrode mixture for a lithium electronic battery with a binder, wherein the binder composition includes a first copolymer of vinylidene fluoride and a compound containing a polar group and a second copolymer of vinylidene fluoride and chlorotrifluoroethylene.
[0013] WO2019 / 167338 (US20210047448) discloses a vinylidene fluoride polymer comprising a first structural unit derived from vinylidene fluoride and a second structural unit derived from a monomer other than vinylidene fluoride. The monomer that becomes the second structural unit is a primary amine, a secondary amine, or a tertiary amine having at least one of a hydroxyl group and a carboxyl group, and the content of the second structural unit is 0.05 to 20.0 mol%.
[0014] JP2019160651 discloses a vinylidene fluoride copolymer with an ethoxylated acrylate comonomer produced by suspension polymerization, having an intrinsic viscosity of 0.1 to 5.0 dL / g.
[0015] Electrodes used in energy storage devices, including but not limited to batteries, capacitors, supercapacitors, non-aqueous secondary batteries, etc.
[0016] The art does not mention functionalized vinylidene fluoride copolymers obtained by copolymerizing vinylidene fluoride with functionalized comonomers, which result in branched, non-linear structures, and their performance as binders for battery electrode compositions. In fact, US8337725 specifically teaches that linear vinylidene fluoride copolymers are very desirable in this application.
[0017] For commercial Solvay products ( 5130), believed to be produced according to US8337725, detailed size exclusion chromatography (SEC) analysis revealed 7 wt% branched structure, expressed as wt% of the molar mass distribution exhibiting branching, as indicated by a slope (α) ≤ 0.5 in a Mark-Houwink plot of logarithmic intrinsic viscosity versus molar mass (see Striegel, Yau, Kirkland, Bly, Modern Size-Exclusion Liquid Chromatography, 2nd edition, 2009). Test methods are described in the Examples section below. The product is considered linear (defined as <10 wt% branched structure).
[0018] Vinylidene fluoride copolymers can be used as binders in electrode preparations used in lithium electronic batteries. As the demand for higher battery performance increases, the need to reduce the binder content in the electrode also increases. In order to reduce the binder content, it is important to improve the performance of the binder material. This performance can be determined through adhesion testing, where the formulated electrode is subjected to a peel test. An increase in the peel value obtained from this test translates into improved adhesion performance and the potential to reduce the overall binder loading, increase the active material loading and increase the battery capacity. Here, we present the use of non-linear vinylidene fluoride copolymers in this application, which exhibit excellent peel adhesion properties.
[0019] The present invention is directed to solving the above problems by providing non-linear fluorinated copolymers comprising vinylidene fluoride, optionally fluorinated olefinic comonomers and functionalized comonomers. It has been found that vinylidene fluoride / functionalized comonomer copolymers containing branched structures (branching degree ≥ 10 wt%) exhibit excellent adhesion to metal foils (measured as electrode peel strength). These copolymers are made by using low temperature initiators having a 10 hour half-life temperature of less than or equal to 53°C. Summary of the invention
[0020] The present invention relates to a non-linear vinylidene fluoride copolymer comprising VDF, an optional fluorinated olefinic comonomer and a functionalized comonomer. The present invention also relates to a suspension process for forming a copolymer of vinylidene fluoride and comonomer(s).
[0021] The present invention further encompasses a method for preparing a fluorinated copolymer in an aqueous reaction medium comprising:
[0022] a) at least one low temperature initiator, a stabilizer, at least vinylidene fluoride and a functionalized comonomer, optionally a fluorinated comonomer,
[0023] b) initiating copolymerization of vinylidene fluoride and the functionalized comonomer under stirring, heating and superatmospheric pressure.
[0024] The present invention also relates to articles formed from the fluorinated copolymers. These articles can be used in applications such as electrodes or separators for batteries.
[0025] The present invention also relates to a formulation comprising a vinylidene fluoride copolymer in a solvent and may further comprise activated carbon and metal chalcogenide particles selected from the group consisting of lithium iron phosphate (LFP), lithium nickel manganese cobalt oxide (NMC), lithium manganese cobalt oxide, lithium nickel cobalt aluminum oxide, lithium manganese oxide and lithium nickel manganese oxide.
[0026] Aspects of the Invention
[0027] Aspect 1. A non-linear fluorinated copolymer comprising:
[0028] At least 87.0 mol% of vinylidene fluoride and
[0029] 0.01 to 3.0 mol % of at least one functionalized comonomer of Formula 1:
[0030]
[0031] wherein R1, R2, and R3 are the same or different and are independently a hydrogen atom or a C1-C3 hydrocarbon group, and R4 is hydrogen or a C1-C3 hydrocarbon group containing at least one hydroxyl group. 16 hydrocarbon part;
[0032] and optionally at least one fluorinated olefinic comonomer,
[0033] wherein the non-linear fluorinated copolymer contains at least 10 wt. % branched structure, preferably at least 15 wt. % branched structure and more preferably at least 20 wt. % branched structure as measured by size exclusion chromatography and
[0034] The non-linear fluorinated copolymer has an average primary particle size greater than 10 microns.
[0035] Aspect 2. The non-linear fluorinated copolymer according to aspect 1, wherein the fluorinated olefinic comonomer is selected from the group consisting of tetrafluoroethylene (TFE), chlorotrifluoroethylene (CTFE), and hexafluoropropylene (HFP).
[0036] Aspect 3. The non-linear fluorinated copolymer of aspect 1 or 2, wherein the at least one functionalized comonomer comprises formula 1, wherein R4 is hydrogen.
[0037] Aspect 4. The non-linear fluorinated copolymer of any one of aspects 1 to 3, wherein the at least one functionalized comonomer comprises acrylic acid.
[0038] Aspect 5. The non-linear fluorinated copolymer of any one of aspects 1 to 4, wherein the content of the functionalized comonomer incorporated into the polymer is 0.01 to 2.0 mol % of the total non-linear fluorinated copolymer.
[0039] Aspect 6. The non-linear fluorinated copolymer according to any one of aspects 1 to 5, wherein the fluorinated olefinic comonomer accounts for up to 10.0 mol %, preferably up to 5.0 mol %, of the total monomer units in the non-linear fluorinated copolymer.
[0040] Aspect 7. The non-linear fluorinated copolymer of any one of aspects 1 to 6, wherein the fluorinated olefinic comonomer comprises HFP.
[0041] Aspect 8. The non-linear fluorinated copolymer of any one of aspects 1 to 7, wherein the fluorinated olefinic comonomer comprises at least 90.0 mol % VDF and 0.1 to 9.99 mol % HFP.
[0042] Aspect 9. The nonlinear fluorinated copolymer according to any one of aspects 1 to 8, wherein a solution of the nonlinear fluorinated copolymer containing 9.0 wt% of the nonlinear fluorinated copolymer in N-methyl-2-pyrrolidone has a viscosity of 4000 mPa·s or more and less than 45000 mPa·s, preferably 5000 mPa·s or more and less than 30000 mPa·s, and most preferably 5000 mPa·s or more and less than 20000 mPa·s, when measured at a controlled shear rate of 3.36 rpm at 23°C.
[0043] Aspect 10. The non-linear fluorinated copolymer according to any one of aspects 1 to 9, wherein the proportion of randomly distributed functionalized comonomers is less than 37%.
[0044] Aspect 11. A method for preparing a nonlinear fluorinated copolymer as described in any one of aspects 1 to 10, wherein the method comprises polymerizing vinylidene fluoride and
[0045] 0.01 to 3.0 mol % based on the total monomer feed of at least one functionalized comonomer of Formula 1:
[0046]
[0047] wherein R1, R2, and R3 are the same or different and are independently a hydrogen atom or a C1-C3 hydrocarbon group, and R4 is hydrogen or a C1-C3 hydrocarbon group containing at least one hydroxyl group. 16 hydrocarbon part;
[0048] and optionally at least one fluorinated olefinic comonomer,
[0049] The 10-hour half-life temperature of the low-temperature initiator is less than or equal to 53°C, preferably less than or equal to 51°C.
[0050] Aspect 12. The method according to aspect 11, wherein the low temperature initiator comprises at least one of n-propyl peroxydicarbonate (NPP), isopropyl peroxydicarbonate (IPP), acetylcyclohexanesulfonyl peroxide or diisobutyryl peroxide.
[0051] Aspect 13. A method as described in aspect 11 or 12, wherein the low temperature initiator is added to the reaction mixture in an amount of about 0.01 to about 5.0 weight percent based on the total monomer weight, and preferably added in an amount of about 0.05 to about 2.5 weight percent based on the total monomer weight.
[0052] Aspect 14. The method according to any one of aspects 11 to 13, wherein the pressure during the polymerization is 280-40,000 kPa, preferably 2,000-20,000 kPa.
[0053] Aspect 15. The method of any one of aspects 11 to 14, wherein the functionalized comonomer is added continuously to the polymerization reaction.
[0054] Aspect 16. The method of any one of aspects 11 to 14, wherein the functionalized comonomer is added discontinuously to the polymerization reaction.
[0055] Aspect 17. A composition for a lithium electronic battery, comprising the nonlinear fluorinated copolymer as described in any one of aspects 1 to 10, an active material, a non-aqueous solvent and a conductive material, and optionally a viscosity modifier.
[0056] Aspect 18. A composition as described in Aspect 17, comprising: (a) a non-linear fluorinated copolymer in an amount of 0.5 to 5.0 wt. %, preferably 0.5 to 3.0 wt. %, relative to the total weight of (a) + (b) + (c); (b) a conductive material in an amount of 0.5 to 5.0 wt. %, preferably 0.5 to 3.0 wt. % relative to the total weight of (a) + (b) + (c); (c) an active material, preferably a composite metal, in an amount of 90 to 99 wt. %, preferably 94 to 99 wt. %.
[0057] Aspect 19. An electrode for a lithium electronic battery obtained by applying the composition of aspect 18 to a metal film and drying the coating.
[0058] Aspect 20. A lithium electronic battery having the electrode of Aspect 19.
[0059] Aspect 21. An article comprising the non-linear fluorinated copolymer of any one of aspects 1 to 10. DETAILED DESCRIPTION
[0060] "Copolymer" is used to refer to a polymer having two or more different monomer units.
[0061] "Polymer" may refer to a homopolymer or a copolymer.
[0062] "Linear" is used according to the definition well known in the art and refers to a polymer chain having a single chain structure and only two end groups. (RJ Young and PA Lovell, Introduction to Polymers, 2nd edition, page 3, London, 1991.) In this case, the polymer chain contains only the specified (comonomer) units and does not have any other structural changes, such as any length or number of additional bonded chains ("branches").
[0063] "Non-linear" is used according to the definition well known in the art to refer to a polymer chain with one or more additional polymer chains bonded to the main linear polymer chain at "branch points". (RJ Young and PA Lovell, Introduction to Polymers, 2nd edition, pages 3 and 4, London, 1991.) The (one or more) additional polymer chains can have any length from two monomer units to a plurality of monomer units. The monomer units comprising the branches can be the same or different from the monomer units in the main linear chain, but are generally derived from the same monomer units present in the main chain. The branches themselves can have additional branches, which are as previously described with respect to the number and composition of the monomer units.
[0064] "Branch point" is used as defined in the art and refers to a polymer backbone atomic unit to which a first monomer unit comprising a branch is bonded. For fluorinated olefinic polymers, the branch point is typically a backbone carbon atom.
[0065] Some special cases of "branching" with "branch points" are known, such as "star", "graft", "comb", "brush", "chimera", "hyperbranching" and "dendritic" structures. (N. Hadjichristidis et al., Chem. Rev. 2001, 101, 3747-3792.) All of these structural variations are considered and included in the definition of "non-linearity" related to changes in the "branching" structure. As mentioned above, the composition of the branches in these special cases can be the same or different monomer compositions, and can also contain monomer units in block, random or gradient configurations.
[0066] For the purposes of the present invention, the terms "non-linear" and "branched" have the same meaning and are used interchangeably.
[0067] "Olefinic comonomer" refers to a comonomer having a polymerizable carbon-carbon double bond. Olefinic polymers are polymers made from olefinic monomers.
[0068] The term "initiator" and the expressions "radical initiator" and "free radical initiator" refer to a chemical that is capable of providing a source of free radicals by decomposition, which can be generated spontaneously under ambient conditions or by exposure to an added external stimulus such as heat or light. The term "free radical" and the expression "free radical" refer to a chemical species that contains at least one unpaired electron.
[0069] "Low temperature initiator" refers to an organic free radical initiator whose 10-hour half-life is less than or equal to 53°C. "Half-life" is used to describe the rate at which a molecule that can be thermally decomposed into free radical species undergoes this reaction. The half-life value is the time required for half of the total number of unit material samples to decompose at a certain temperature. "10-hour half-life" refers to the temperature at which any given compound undergoes half-life within 10 hours. The initiator used in the present invention is an organic initiator whose 10-hour half-life temperature is less than or equal to 53°C, preferably less than or equal to 51°C (for relevant examples of low temperature initiators, see Polymer Synthesis, Volume 1, 1992, Part 2 - Free Radical Initiation, Table II; or "Initiators for High Polymers" Technical Product Brochure, Akzo-Nobel; or Organic Peroxides , Volume 1, D. Swern, ed., Wiley-Interscience, 1970, Table 20).
[0070] All cited references are incorporated herein by reference. As used herein, percentages shall refer to weight percentages unless otherwise indicated.
[0071] The present invention discloses a branched fluorinated copolymer comprising vinylidene fluoride, a functionalized comonomer and an optional fluorinated olefinic comonomer.
[0072] The optional fluorinated olefinic comonomer is preferably selected from the group consisting of tetrafluoroethylene (TFE), chlorotrifluoroethylene (CTFE) and hexafluoropropylene (HFP).
[0073] The functional comonomer is preferably acrylic acid.
[0074] According to one embodiment, the fluorinated copolymer comprises vinylidene fluoride and 0.01 to 3.0 mol % of at least one ("one or more") functionalized comonomer.
[0075] According to one embodiment, the functionalized comonomer is randomly incorporated into the copolymer, as determined by nuclear magnetic resonance spectroscopy ( 19 F NMR), its proportion is less than 40% of the total hydrophilic monomers fed to the reaction, calculated by the following equations 1 and 2:
[0076] Equation 1: (Total moles of dry solids produced * mole % of comonomer incorporated) = moles of comonomer incorporated
[0077] Equation 2: (Equation 1) / (Total moles of comonomer fed) = Ratio of isolated functionalized comonomer incorporated
[0078] The proton decoupling of the polymer powders was recorded under the following conditions 19 F NMR spectrum.
[0079] Instrument: Bruker AVANCE AC 400FT NMR spectrometer
[0080] Test conditions:
[0081] Frequency: 376MHz
[0082] Test solvent: DMSO-d
[0083] Test temperature: 25℃
[0084] Scan times: 2048
[0085] analyze 19 F NMR spectroscopy was used to determine the content of hydrophilic comonomer in the polymer. Specifically, the area integral of the peak(s) at -94 ppm (integrated value) corresponding to the four fluorine atoms present in the structural unit derived from vinylidene fluoride adjacent to the incorporated hydrophilic comonomer unit was divided by the intensity of all peaks assigned to fluorine atoms in the spectrum.
[0086] Another object of the present invention is a novel method for producing the above nonlinear copolymer. The method according to the present invention advantageously comprises polymerizing vinylidene fluoride (VDF) monomer and functionalized comonomer in an aqueous medium in the presence of a low temperature initiator in a reaction vessel, the method comprising feeding an aqueous solution containing the functionalized comonomer; and maintaining the pressure in the reaction vessel above the critical pressure of vinylidene fluoride.
[0087] The present invention further encompasses a method for preparing a vinylidene fluoride copolymer in an aqueous reaction medium, comprising:
[0088] a) at least one low temperature initiator, a stabilizer, vinylidene fluoride, optionally at least one fluorinated olefinic comonomer and a functionalized comonomer,
[0089] b) initiating copolymerization of the vinylidene fluoride, optional fluorinated olefinic comonomer and the functionalized comonomer under stirring, heating and superatmospheric pressure.
[0090] In a preferred embodiment, the present invention comprises a non-linear copolymer comprising vinylidene fluoride having greater than 87 mole percent vinylidene fluoride monomer units, preferably greater than 90 mole percent and most preferably greater than 95 mole percent vinylidene fluoride monomer units.
[0091] Fluorinated olefinic comonomers
[0092] The present invention is a vinylidene fluoride copolymer, which may optionally have a fluorinated olefinic comonomer. Examples of fluorinated olefinic comonomers "fluorinated monomers" may be selected from the group consisting of tetrafluoroethylene (TFE), trifluoroethylene (TrFE), chlorotrifluoroethylene (CTFE), 1,2-difluoroethylene, perfluorobutylethylene (PFBE), hexafluoropropylene (HFP), vinyl fluoride (VF), pentafluoropropylene, 2,3,3,3-tetrafluoropropylene, trifluoropropylene, fluorinated (alkyl) vinyl ethers [e.g., perfluoroethyl vinyl ether (PEVE), perfluoro-2-propoxypropyl vinyl ether, perfluoromethyl vinyl ether (PMVE), perfluoropropyl vinyl ether (PPVE), perfluorobutyl vinyl ether (PBVE), long chain perfluorinated vinyl ethers], one or more partially or completely Fluorinated alpha-olefins [e.g., 3,3,3-trifluoro-1-propene, 2-trifluoromethyl-3,3,3-trifluoropropene, 1,2,3,3,3-pentafluoropropene, 3,3,3,4,4-pentafluoro-1-butene, hexafluoroisobutylene (HFIB)], fluorinated dioxoles [e.g., perfluoro(1,3-dioxole) and perfluoro(2,2-dimethyl-1,3-dioxole) (PDD)], partially fluorinated or perfluorinated C4 and higher alpha olefins, partially fluorinated or perfluorinated C3 and higher cycloolefins, allyl, partially fluorinated allyl or fluorinated allyl monomers, such as 2-hydroxyethyl allyl ether or 3-allyloxypropylene glycol, and combinations thereof.
[0093] Preferably, the optional fluorinated olefinic comonomer is selected from the group consisting of tetrafluoroethylene (TFE), chlorotrifluoroethylene (CTFE) and hexafluoropropylene (HFP).
[0094] Functionalized comonomers
[0095] The copolymers of the present invention contain functionalized comonomer units. The functionalized comonomer is defined by Formula 1:
[0096] Formula 1
[0097] wherein R1, R2, and R3 are the same or different and are independently a hydrogen atom or a C1-C3 hydrocarbon group, and R4 is hydrogen or a C1-C3 hydrocarbon group containing at least one hydroxyl group. 16 Hydrocarbon part.
[0098] In some embodiments, only one of R1, R2, and R3 is hydrogen.
[0099] In some embodiments, two of R1, R2, and R3 are hydrogen.
[0100] One or more functionalized comonomers can be used in combination with VDF and optionally one or more fluorinated olefinic comonomers to form the copolymers of the present invention.
[0101] Non-limiting examples of functionalized comonomers include acids, such as acrylic acid and methacrylic acid.
[0102] The amount of functionalized comonomers can be, for example, about 0.01 to 3.0 mol% based on total monomers. Preferably, they are used in an amount of about 0.01 to about 2.0 mol% based on total monomers. In various embodiments, the total amount of (one or more) functionalized comonomers is at least 0.01 mol%, at least 0.05 mol%, at least 0.10 mol% based on total monomers. In other embodiments, the total amount of functionalized comonomers is no more than 3.0 mol%, or preferably no more than 2.0 mol% based on total monomers. For ease of handling, functionalized comonomers can be used in solutions such as aqueous solutions.
[0103] Technology
[0104] The vinylidene fluoride copolymer of the present invention can be obtained by copolymerizing vinylidene fluoride, one or more functionalized comonomers represented by Formula 1, and optionally additional fluorinated olefinic comonomers in a suspension polymerization process.
[0105] Suspending agents are used in the process to provide stability to the copolymer particles during suspension polymerization. In suspension polymerization, water is used as the dispersion medium, and 0.005 to 1.0 parts by weight, preferably 0.01 to 0.4 parts by weight of suspending agent may be added per 100 parts by weight of all monomers used for copolymerization.
[0106] Suspending agents include, but are not limited to, methylcellulose, methoxylated methylcellulose, propoxylated methylcellulose, hydroxyethylcellulose, hydroxypropylcellulose, polyvinyl alcohol, polyethylene oxide, and gelatin. Preferred suspending agents include functionalized cellulose, fully hydrolyzed and partially hydrolyzed poly(vinyl alcohol) and inorganic clays, as described in Handbook of Polymer Reaction Engineering, Chapter 5, Free-radical Polymerization: Suspension, edited by BW Brooks, Dr. T. Meyer, Prof. J. Keurentjes, Wiley, 2005, which is incorporated herein by reference in its entirety.
[0107] Initiator
[0108] Low temperature initiator is added to the reaction mixture in an amount sufficient to initiate polymerization and maintain the polymerization at a desired reaction rate. The order of addition can vary according to the desired process characteristics. In one embodiment, all low temperature initiators are added before the polymerization process begins. Low temperature initiator can be added to the reaction mixture in an amount of about 0.01 to about 5.0 weight percent of total monomers, and preferably added in an amount of about 0.05 to about 2.5 weight percents of total monomers [total monomers refer to vinylidene fluoride, (one or more) compounds represented by Formula 1, and optional other fluorinated olefinic comonomers selected as needed].
[0109] The example of suitable low temperature initiator comprises peroxide, peroxyester, peroxydicarbonate and azo compound.Low temperature initiator can comprise organic peroxide, for example alkyl peroxide, dialkyl peroxide, diacyl peroxide, peroxydicarbonate, peroxyester or its mixture.Preferred peroxydicarbonate initiator comprises acetyl cyclohexanesulfonyl peroxide, diisobutyryl peroxide, di-n-propyl peroxydicarbonate, diisopropyl peroxydicarbonate.
[0110] For low-temperature initiators that are substantially insoluble in water, it is advantageous to pre-disperse them in water. The method of dispersing low-temperature initiators in water is a method generally known in the art for producing an oil-in-water emulsion, wherein water and an immiscible component (here, an initiator) are subjected to high shear mixing, and a surfactant or other stabilizer is usually added, as described in "Encyclopedic Handbook of Emulsion Technology, First Edition, Johan Sjoblom, Marcel-Dekker, New York, 2001", which is incorporated herein by reference in its entirety. When the initiating substance has low thermal stability (as evidenced by a 10-hour half-life temperature below 53°C), it is particularly advantageous to treat the initiating substance in this manner. The presence of water in the low-temperature initiator dispersion or emulsion provides a heat dissipation pathway for the decomposition heat, and reduces the possibility of a thermal runaway reaction of the low-temperature initiator itself, greatly improving the safety of the process. It is further advantageous that the surfactant or dispersant used to stabilize the low temperature initiator / water dispersion or emulsion is compatible with the copolymerization reaction, and most advantageously, the surfactant or dispersant used to stabilize the low temperature initiator / water dispersion is the same as the surfactant or dispersant used to stabilize the reaction emulsion or suspension.
[0111] Chain transfer agent
[0112] Chain transfer agents are optionally added in the polyreaction to regulate the molecular weight of the product. They can be added to the polyreaction in a single portion at the start of the reaction, or added incrementally or continuously throughout the reaction. The addition amount and addition mode of the chain transfer agent depend on the activity of the specific chain transfer agent used, and the molecular weight required for the polymer product. The amount of the chain transfer agent added to the polyreaction is preferably about 0.0 to about 5.0 weight percent based on the gross weight of the monomer added to the reaction mixture, more preferably about 0.05 to about 3.0 weight percent.
[0113] Oxygenated compounds such as alcohols, carbonates, ketones, esters and ethers can be used as chain transfer agents. Examples of oxygenated compounds that can be used as chain transfer agents include ethyl isopropanol, methyl acetate, diethyl carbonate, acetone, ethanol, n-propanol, acetaldehyde, propionaldehyde, ethyl propionate, and as described in US Patent 4,360,652. Other classes of compounds that can serve as chain transfer agents in the polymerization of halogen-containing monomers include, for example, halogenated hydrocarbons and hydrogen-containing halogenated hydrocarbons, and chlorohydrocarbons such as carbon tetrachloride. Simple alkanes or branched alkanes such as ethane, propane or 2-ethylhexane can also be used as chain transfer agents.
[0114] Buffer
[0115] The polymerization reaction mixture may optionally contain a buffer to maintain a controlled pH throughout the polymerization reaction. The pH is preferably controlled within the range of about 2.0 to about 8.0 to minimize undesirable color development in the product.
[0116] The buffer may include an organic or inorganic acid or an alkali metal salt thereof, or a base or salt of such an organic or inorganic acid having at least one pK in the range of about 4.0 to about 10.0, preferably in the range of about 4.5 to about 9.5. a Value and / or pK b Value. Preferred buffers in the practice of the present invention include, for example, phosphate buffer and acetate buffer. "Phosphate buffer" is a salt or a mixture of salts of phosphoric acid. "Acetate buffer" is a salt of acetic acid.
[0117] Industrial use of vinylidene fluoride and functionalized comonomers, optionally with other fluorinated olefinic monomers of linear copolymers. However, the existing methods for producing such linear polymers have the problem of low reaction productivity, resulting in difficulty in supplying sufficient amounts of material to a rapidly growing market. In some embodiments, the present invention provides high productivity of vinylidene fluoride copolymer polymerization, while maintaining or improving their adhesion properties to metal films. High productivity means that the run time of the polymerization reaction is less than 12 hours. Reducing the polymerization time so that the process is more efficient (faster) and reducing the energy used is of great interest to people. In some embodiments of the present invention, the polymerization run time is less than 12 hours, may be less than 10 hours, and most preferably less than 8 hours. The higher the process efficiency, the higher the productivity.
[0118] Copolymerization conditions
[0119] Based on the low temperature initiator system selected, the temperature for polymerization can vary, for example, from 20-100 degrees Celsius (° C.) The polymerization temperature is preferably 35-75° C., and most preferably 35-60° C.
[0120] Typically, the process of the present invention is carried out at a temperature of 20 to 70° C., preferably with an upper limit of 60° C., at least 35° C., preferably at least 40° C., more preferably at least 45° C. The temperature used during the polymerization process may vary or may be maintained at a constant temperature.
[0121] The pressure used for the polymerization can vary between 280-40,000 kilopascals (kPa), depending on the capacity of the reaction equipment, the low temperature initiator system selected, and the choice of monomers. The polymerization pressure is preferably between 2,000-20,000 kPa.
[0122] Optionally, the functionalized comonomer can be fed continuously throughout the polymerization process. In the case of discontinuous feeding, the feed distribution can be provided to the reactor in terms of rate and / or in a discontinuous manner. Therefore, the functionalized comonomer feed can appear in multiple aliquots throughout the polymerization process.
[0123] Incremental addition of VDF or fluorinated olefinic comonomers may also be made during the polymerization. In one embodiment, all of the required VDF monomer is introduced before the start of polymerization.
[0124] By conducting aqueous suspension polymerization under the above conditions, vinylidene fluoride, the compound represented by Formula 1 and other optional fluorinated olefinic comonomer(s) are copolymerized to obtain the vinylidene fluoride copolymer of the present invention.
[0125] A maximum of 10.0 weight percent (relative to the total monomer feed) of the compound represented by Formula 1 is fed into the polymerization process, preferably less than 4 weight percent, more preferably 3 weight percent (based on the total monomers fed to the polymerization reaction) or less of the compound represented by Formula 1.
[0126] The polymerization occurs under stirring or other agitation. The stirring / agitation can be constant, or the rate can be changed to optimize the process conditions during the polymerization. In one embodiment, a variety of stirring speeds and a variety of temperatures are considered to control the reaction.
[0127] The polymerization reaction according to the present invention can be carried out by adding water (preferably deionized water), a suspending agent, vinylidene fluoride, optionally at least one fluorinated olefinic comonomer, at least one functionalized comonomer represented by Formula 1, and optionally a chain transfer agent and / or a buffer into the reactor. Before the monomer is introduced, the air is removed from the reactor. Before the reactor is made to reach the desired starting temperature, water is added to the reactor, but other materials can be added before or after the reactor reaches the desired temperature. At least one low temperature initiator is added to start and maintain the polymerization reaction. Additional monomers can be optionally added to supplement the consumed monomers and other materials, such as buffer or chain transfer agents can be optionally added during the polymerization to maintain the reaction and adjust the characteristics of the final product.
[0128] The order of combining the polymerization components may vary, but it is generally preferred that at least a portion of the functionalized comonomer is present in the aqueous reaction medium prior to initiation of polymerization of the fluorinated olefinic comonomer. Additional amounts of the functionalized comonomer may be fed to the reactor during the reaction in the manner described above.
[0129] Alternatively, no additional fluorinated olefinic comonomer is fed to the reactor and the pressure is maintained only by adding the functionalized comonomer in bulk or solution and / or additional ingredients such as low temperature initiators or buffers or simply deoxygenated water.
[0130] When the desired weight of monomer has been fed into the reactor, the monomer feed is terminated. Optionally, additional low temperature initiators are added, and the reaction pressure is allowed to decrease within a suitable time. As the monomer in the reactor is consumed, the reactor pressure decreases. At this point, the feeding of the functionalized comonomer can be continued or stopped. If the feeding of the functionalized comonomer is stopped, the content of the functionalized comonomer of the multipolymer produced in this reaction stage will be lower, or will not contain the functionalized comonomer.
[0131] After the copolymerization reaction is completed, the reactor is raised to ambient temperature and the residual unreacted monomers are vented to atmospheric pressure. The aqueous reaction medium containing the copolymer is then recovered from the reactor. The product consists of a mixture of reaction components, i.e., water, residual functionalized comonomers, low temperature initiators (and / or decomposition products of the initiators), and copolymer solids.
[0132] Product handling
[0133] The copolymerization product is a solid that can be separated from the aqueous component and dried by conventional methods known in the art, including filtration or other suitable solid / liquid separation techniques such as centrifugation. Once separated, the solid product can be purified by washing with deionized water or other techniques, and can be dried to be used as a powder, which can be further processed into granules, pellets, etc.
[0134] Characterization of the non-linear copolymers of the invention
[0135] The fluorinated copolymers of the present invention are non-linear. The fluorinated copolymers contain at least 10 wt % branched structure as measured by size exclusion chromatography using a Mark-Houwink plot as described in Striegel, Yau, Kirkland, Bly, Modern Size-Exclusion Liquid Chromatography, Second Edition (2009), which is incorporated herein by reference in its entirety, preferably at least 15 wt % branched structure and most preferably at least 20 wt % branched structure. The test method is described below.
[0136] The primary particle size of the copolymer of the present invention is greater than 10 microns. This can be measured by optical microscopy using an eyepiece graticule and a stage micrometer.
[0137] Preferably, the functionalized comonomer has less than 40% of isolated functionalized comonomer in the main chain based on molar percentage. The copolymer of the present invention may have a proportion of isolated functionalized comonomer of less than 37%, preferably less than 36%. 19 F NMR determination.
[0138] Preferably, the solution viscosity of the fluorinated copolymer is such that a solution of 9 wt.% of the vinylidene fluoride copolymer in N-methyl-2-pyrrolidone has a viscosity of equal to or greater than 2000 mPa·s, preferably equal to or greater than 5000 mPa·s, most preferably equal to or greater than 6000 mPa·s and less than 30000 mPa·s, less than 20000 mPa·s, preferably less than 15000 mPa·s, measured at 23° C. with a controlled shear rate of 3.36 revolutions / second. The solution viscosity is measured using a Brookfield DV3 rotational viscometer comprising a spindle of type SC4-34, using a circulating temperature controlled bath set at 23° C. and corresponding to a shear rate of 3.36 s -1 The rotation rate.
[0139] Electrodes and batteries
[0140] The present invention also relates to components of lithium electronic batteries, such as electrodes or separators, comprising the nonlinear fluorinated copolymer. The nonlinear fluorinated copolymer can be used as a binder in the electrode formulation, whether cathode or anode. The present invention encompasses a battery comprising the fluorinated copolymer described herein.
[0141] The invention also relates to a formulation comprising a nonlinear fluorinated copolymer in solution. Another object of the invention is the use of the nonlinear fluorinated copolymer composition as a binder, in particular for forming electrodes for lithium batteries and / or double-layer capacitors. Another object of the invention is an electrode-forming composition comprising a solvent, a nonlinear fluorinated copolymer, an active material (powdered electrode material) and optionally a conductive material and / or a viscosity modifier.
[0142] Electrode slurry formulation
[0143] When the desired electrode to be produced is a cathode, the prepared slurry required for forming the cathode comprises a solvent, a polymer binder, an active material and a conductive material. The active material and the conductive material are preferably in a dry powdered state. When the electrode is an anode, the slurry forming the anode comprises a solvent, a polymer binder and a conductive material. The conductive material can be one or more of the following: coke, carbon black, graphite, activated carbon, carbon fiber, silicon, graphene, graphene oxide and carbon nanotubes.
[0144] When the nonlinear fluorinated copolymer of the present invention is used as a binder, a binder solution of the nonlinear fluorinated copolymer is generally prepared. In order to obtain the binder solution of the nonlinear fluorinated copolymer, preferably 0.1-10.0 parts by weight, especially 1.0-5.0 parts by weight of the nonlinear fluorinated copolymer is dissolved in 100 parts by weight of an organic solvent. Any suitable organic solvent that dissolves the polymer binder can be used.
[0145] According to the present invention, the organic solvent used to dissolve the nonlinear fluorinated copolymer binder to provide the nonlinear fluorinated copolymer binder solution is preferably a polar organic solvent, examples of which include: N-methyl 2-pyrrolidone (NMP), dimethyl sulfoxide (DMSO), N,N-dimethylformamide (DMF), triethyl phosphate (TEP), acetone, tetrahydrofuran, methyl ethyl ketone (MEK), methyl isobutyl ketone (MiBK), ethyl acetate (EA), butyl acetate (BA), dimethyl carbonate (DMC), diethyl carbonate (DEC) or methyl ethyl carbonate (MEC), N-ethyl-2-pyrrolidone, N,N-dimethylacetamide, hexamethylphosphoramide, dioxane, tetramethylurea, (1R)-7,8-dioxabicyclo[3.2.1]octan-2-one [Cyrene from MilliporeSigma], TM] and trimethyl phosphate (TMP). These solvents can be used alone or in combination of two or more. The polymer binder composition is dissolved in the solvent by applying stirring or heating to prepare a polymer binder solution.
[0146] The active material comprises a lithium metal compound known in the art. See, for example, US2018 / 0076444 and US2020373560. The active material for the cathode is typically a lithium transition metal alloy chalcogenide, such as lithium iron phosphate (LFP), lithium nickel manganese cobalt oxide (NMC), lithium manganese cobalt oxide, lithium nickel cobalt aluminum oxide, lithium manganese oxide, and lithium nickel manganese spinel.
[0147] Conductive materials may be added to improve the conductivity of the resulting composite electrode layer formed by applying and drying the electrode-forming composition of the present invention. Conductive materials include, but are not limited to, carbonaceous materials such as graphite powder and fibers, carbon black, Super Carbon black, C-NERGY TM Carbon black, Ketjen black, Denka black, thermal black, channel black, carbon fiber, carbon nanotubes, acetylene black, metal powder and fiber, such as nickel and aluminum. The preferred conductive material is carbon black.
[0148] In one embodiment, the nonlinear fluoropolymer binder material can be used as a component of an electric double layer capacitor. The active material for the electric double layer capacitor preferably includes fine particles or fibers, such as activated carbon, activated carbon fibers, silica or alumina particles, with an average particle (or fiber) diameter of 0.05-100 μm and a specific surface area of 100-3000 m 2 / g, that is, it has a relatively small particle (or fiber) diameter and a relatively large specific surface area compared with those active materials used in batteries.
[0149] The solid content (wt%) of the electrode slurry comprising the fluorinated copolymer binder, active material and conductive material is preferably in the range of 71 to 87 wt%, more preferably about 75 to 85 wt%. The solid content (wt%) of the electrode slurry may be between 80 wt% and 87 wt%.
[0150] The content of the solid components of the cathode formulation with active material, conductive material and polymer binder can vary relative to the amount of each component. Preferably, the amount of active material is about 90-99 weight % of the total solids; the amount of conductive material is about 0.5 to 5.0 weight % of the total solids, and the amount of fluorinated copolymer binder is about 0.5 to 5.0 weight % of the total weight of active material, conductive material and fluorinated copolymer binder. The electrode slurry may optionally contain other additives, such as viscosity modifiers. Preferably, the electrode slurry is free of additives.
[0151] Forming electrodes
[0152] The fluorinated copolymer binder is blended with one or more active powdered electrode forming materials in the form of a solvent solution or dispersion to form a slurry dispersion or paste. The dispersion or paste is then applied to one or both surfaces of a conductive substrate using a technique known in the art for applying a uniform wet coating, and dried to form a dried composite electrode layer. The electrode layer can then be compressed by any method known in the art, including the rolling as shown in US5776637 and US6200703, wherein the fluoropolymer binder is dissolved in NMP and processed into an electrode. In another method, a polymer binder in powder form is blended with one or more active powdered electrode forming materials, and then a solvent is added to form a slurry dispersion or paste. Subsequent application, drying and rolling steps are the same as above.
[0153] The electrode slurry composition can be applied to at least one surface of the metal current collector, preferably on both surfaces, and dried at an elevated temperature (e.g., 50-170° C.) to form a dry composite electrode layer. Any metal having high conductivity and no reactivity within the voltage range of the battery to be constructed can be used as a metal current collector, and the composite electrode layer is firmly adhered to the metal current collector. Such substrates include metal foils or wire meshes, non-limiting examples of which include iron, stainless steel, steel, copper, lithium, aluminum, nickel, silver, or titanium, or a combination thereof.
[0154] Other Uses
[0155] The nonlinear functionalized polyvinylidene fluoride of the present invention can be used for membrane / antifouling, fiber (carbon fiber) sizing, tie layer of multilayer sheet, adhesive (general purpose), water or proton permeation membrane, battery separator coating, (fluorinated) polymer blending compatibilizer, paint or industrial coating component.
[0156] The characteristics of the invention and the various advantages it offers will become more apparent on reading the following embodiments, provided as illustrative and non-limiting examples.
[0157] Example
[0158] The particle size of the polymer powder was measured using laser diffraction and a Microtrac S3500 particle size analyzer. The data are volume average particle size (diameter).
[0159] Can be used 19 F-NMR was used to determine the mole percentage of vinylidene fluoride in the copolymer.
[0160] The weight percent (wt%) of branched structures contained in the non-linear fluoropolymer was determined using the following method:
[0161] The absolute molar mass and intrinsic viscosity of the sample were measured using multi-detector size exclusion chromatography. The absolute molar mass obtained by multi-detector scattered light and the intrinsic viscosity obtained by differential viscometry were combined in the form of a Mark-Houwink plot to determine the molecular structure, defined by the Mark-Houwink slope (α) at each molar mass value. The branched molar mass is determined based on the molar mass corresponding to the change in the slope of the Mark-Houwink plot from (α)>0.5 to (α)≤0.5. When (α)>0.5, the material is considered to be linear. When (α)≤0.5, the material is considered to be branched (non-linear). The weight % branched structure is determined by integrating the molar mass distribution area of the sample with a molar mass corresponding to a Mark-Houwink slope (α)≤0.5.
[0162] Sample preparation: The polymer was dissolved in DMSO containing 0.1% LiCl at 1.0 mg / mL, gently shaken and heated at 90° C. for 72 hours. The sample solution was analyzed as is without additional filtration.
[0163] Mobile phase: DMSO containing 0.1% LiCl
[0164] Flow rate: 0.50mL / min
[0165] Temperature: 50℃
[0166] Separation unit: Agilent 1200
[0167] Injection volume: 100 μL
[0168] Column: Two PSS PFG analytical linear XL columns and one guard column (inner diameter 7.8 mm × 30 cm, 7 μm)
[0169] Detectors: Wyatt HELEOS 8+ light scattering detector, ViscoStar III differential viscometer and Wyatt T-rEX refractometer.
[0170] Data acquisition and processing software: ASTRA 7
[0171] Example 1: Synthesis
[0172] A cylindrical jacketed autoclave with an internal volume of 17.5 L was equipped with an overhead stirrer, a stirrer shaft with three 45 degree pitched blade stirrers, a thermocouple, and a pressure sensor. A 1.0 wt% deionized water solution of acrylic acid ("AA") was prepared by adding 40.0 g of AA to 3960 g of deionized water. This solution was added to a feed tank connected to a high pressure reciprocating diaphragm pump connected to the autoclave. 4.13 g of METHOCEL was added to the autoclave. K100LV [Dupont] [Hydroxypropyl methylcellulose (HPMC)] was dissolved in 8717 mL of deionized water and loaded into an autoclave. 19.5 g of n-propyl peroxydicarbonate (NPP), 1.0 g of Methocel K100LV and 629.5 g of H2O precooled to 5°C were added to a 1.0 L plastic bottle and the mixture was stirred under high shear for 10 minutes to prepare 650 g of a 3.0 wt% NPP emulsion in deionized water. The entire contents of the emulsion (650 g) were then loaded into an autoclave. The agitator was started at 400 rpm and the autoclave was pressurized to 88 bar (g) (8800 kPa) with vinylidene fluoride (VDF), then the temperature was raised to 50°C and the autogenous pressure increased to 100 to 105 bar (g) (10,000 to 10,500 kPa). The AA solution was fed at a low rate (~50-100 mL / hour) and then additional (VDF) was added to increase the pressure to 115 bar (g) (11,500 kPa). The onset of polymerization was recorded by the drop in reactor pressure, at which time the feed of AA solution was increased and continuously adjusted (300-700 g / hour) to maintain the reactor pressure at 115 bar (g) (11,500 kPa). The reaction continued in this manner for 447 minutes, at which time the AA feed pump was stopped and the autoclave pressure was reduced for 60 minutes. At this point, the autoclave was cooled to 25°C, vented and the product was discharged as a foamy aqueous dispersion. A total of 3661 g of AA solution was added during the reaction time. The solid product was separated from the water by gravity filtration using a porous cloth. The wet solid product was then dried to constant weight in a ventilated convection oven. 1676 g of the dried product was recovered as a white powder.
[0173] Embodiment 2:
[0174] A cylindrical jacketed autoclave with an internal volume of 17.5 L was equipped with an overhead stirrer, a stirring shaft with three 45-degree inclined blade stirrers, a thermocouple, and a pressure sensor. A 1.5 wt% AA deionized water solution was prepared by adding 60.0 g of acrylic acid (AA) to 3940 g of deionized water. The solution was added to a feed tank connected to a high-pressure reciprocating diaphragm pump connected to the interior of the autoclave. 4.13 g of Methocel K100LV was dissolved in 8717 mL of deionized water and loaded into the autoclave. 19.5 g of n-propyl peroxydicarbonate (NPP), 1.0 g of Methocel K100LV, and 629.5 g of H2O precooled to 5°C were added to a 1.0 L plastic bottle, and the mixture was stirred under high shear for 10 minutes to prepare 650 g of a 3.0 wt% NPP deionized water emulsion. The entire contents of the emulsion (650 g) were then loaded into an autoclave. The agitator was started at 400 rpm and the autoclave was pressurized to 88 bar (g) (8800 kPa) with vinylidene fluoride (VDF), then the temperature was raised to 50° C. and the autogenous pressure increased to 100 to 105 bar (g) (10,000 to 10,500 kPa). The AA solution was fed at a low rate (~50-100 mL / hour) and then additional (VDF) was added to increase the pressure to 115 bar (g) (11,500 kPa). The start of polymerization was recorded by the autogenous reduction of the reactor pressure, at which time the feed of AA solution was increased and continuously adjusted (300-700 g / hour) to maintain the reactor pressure at 115 bar (g) (11,500 kPa). The reaction continued in this manner for 459 minutes, at which time the AA feed pump was stopped and the autogenous pressure of the autoclave was allowed to decrease for 60 minutes. At this point, the autoclave was cooled to 25°C, vented and the product was discharged as a foamy aqueous dispersion. A total of 3603 g of AA solution was added during the reaction time. The solid product was separated from the water by gravity filtration using a porous cloth. The wet solid product was then dried to constant weight in a ventilated convection oven. 2825 g of the dried product was recovered as a white powder.
[0175] The degree of branching, randomness and solution viscosity were measured.
[0176] Table 1
[0177]
[0178] S5130 is from Solvay 5130, believed to be made according to US 8337725. Reaction times and randomness reflect data in the patent examples.
[0179] electrode
[0180] The formulation was prepared using a Thinky ARE-310 mixer. After the non-linear fluoropolymer binder solution was added to the carbon black, seven 6.5 mm zirconium beads were added to the Thinky cup. The mixture was mixed at 2000 rpm for 2 minutes, three times for a total of six minutes to produce a conductive material slurry. The active material was added with the first addition of NMP. The active material slurry was mixed at 2000 rpm for one minute, twice. NMP was added and the active material slurry was mixed at 2000 rpm for one minute, twice. The remaining aliquot of NMP was added and mixed at 2000 rpm for one minute between each addition to obtain the electrode slurry. The total mixing time for the entire formulation was 13 minutes.
[0181] The resulting slurry was cast onto an aluminum substrate using a doctor blade. The gap setting on the doctor blade was set to 135 micrometers wet thickness and the resulting wet electrode was placed in a 120°C oven for 30 minutes.
[0182] The dried electrode film thickness is 70-75 microns and the mass loading is 18-20 mg / cm 2 The electrodes were cut into one inch (25.4 mm) strips and fed into a pneumatically controlled calender. The electrodes were compressed to a target thickness of 55 microns. The calendered electrodes were used in the peel testing process.
[0183] The electrode peel strength was measured in a 180° peel test according to ASTM D903.
[0184] Table 2
[0185] ID Functionalized comonomer content (wt%) Electrode peeling force (N / m) Example 1 0.50 195 Example 2 0.70 183 S5130 178*
[0186] (1)*Average value of 3 independent production processes.
[0187] Examples 1 and 2 show exemplary performance as battery electrode binders.
Claims
1. A non-linear fluorinated copolymer comprising: At least 87.0 mol% of vinylidene fluoride and 0.01 to 3.0 mol % of at least one functionalized comonomer of Formula 1: in, R1, R2, and R3 are the same or different and are independently hydrogen or a C1-C3 hydrocarbon group, and R4 is hydrogen or a C1-C3 hydrocarbon group containing at least one hydroxyl group. 16 hydrocarbon part; and optionally at least one fluorinated olefinic comonomer, The nonlinear fluorinated copolymer contains at least 10 wt% branched structure, preferably at least 15 wt% branched structure and more preferably at least 20 wt% branched structure, and the average primary particle size of the nonlinear fluorinated copolymer is greater than 10 microns.
2. The non-linear fluorinated copolymer of claim 1, wherein the fluorinated olefinic comonomer is selected from the group consisting of tetrafluoroethylene (TFE), chlorotrifluoroethylene (CTFE), hexafluoropropylene (HFP), and combinations thereof.
3. The non-linear fluorinated copolymer of claim 1, wherein the at least one functionalized comonomer comprises Formula 1, wherein R4 is hydrogen.
4. The non-linear fluorinated copolymer of claim 1, wherein the at least one functionalized comonomer comprises acrylic acid.
5. The non-linear fluorinated copolymer of any one of claims 1 to 4, wherein the functionalized comonomer content incorporated into the polymer is from 0.01 to 2.0 mol% of the total non-linear fluorinated copolymer.
6. The non-linear fluorinated copolymer of any one of claims 1 to 4, wherein the fluorinated olefinic comonomer represents at most 10.0 mol%, preferably at most 5.0 mol%, of the total monomer units in the non-linear fluorinated copolymer.
7. The non-linear fluorinated copolymer of any one of claims 1 to 4, wherein the fluorinated olefinic comonomer comprises HFP.
8. The non-linear fluorinated copolymer of any one of claims 1 to 4, wherein the fluorinated olefinic comonomer comprises at least 90.0 mol% VDF and 0.1 to 9.99 mol% HFP.
9. The nonlinear fluorinated copolymer according to any one of claims 1 to 4, wherein a solution of the vinylidene fluoride polymer in N-methyl-2-pyrrolidone containing 9.0 wt.% has a viscosity of 4000 mPa·s or more and less than 45000 mPa·s, preferably 5000 mPa·s or more and less than 30000 mPa·s, and most preferably 5000 mPa·s or more and less than 20000 mPa·s, when measured at a controlled shear rate of 3.36 rpm at 23°C.
10. The non-linear fluorinated copolymer as claimed in any one of claims 1 to 4, wherein the proportion of randomly distributed functionalized comonomers is less than 37%.
11. A method for preparing a nonlinear fluorinated copolymer, wherein the method comprises polymerizing vinylidene fluoride and 0.01 to 3.0 mol % based on the total monomer feed of at least one functionalized comonomer of Formula 1: in, R1, R2, and R3 are the same or different and are independently hydrogen or a C1-C3 hydrocarbon group, and R4 is hydrogen or a C1-C3 hydrocarbon group containing at least one hydroxyl group. 16 hydrocarbon part; and optionally at least one fluorinated olefinic comonomer, The 10-hour half-life temperature of the low-temperature initiator is less than or equal to 53°C, preferably less than or equal to 51°C.
12. The method of claim 11, wherein the low temperature initiator comprises at least one of n-propyl peroxydicarbonate (NPP), isopropyl peroxydicarbonate (IPP), acetylcyclohexanesulfonyl peroxide or diisobutyryl peroxide.
13. The method of claim 11 or 12, wherein the low temperature initiator is added to the reaction mixture in an amount of about 0.01 to about 5.0 weight percent based on the total monomer weight, and preferably in an amount of about 0.05 to about 2.5 weight percent based on the total monomer weight.
14. The process of claim 11, wherein the pressure during polymerization is 280-40,000 kPa, preferably 2,000-20,000 kPa.
15. The process of claim 11 or 12, wherein the functionalized comonomer is added continuously to the polymerization reaction.
16. The method of claim 11 or 12, wherein the functionalized comonomer is added discontinuously to the polymerization reaction.
17. A composition for a lithium electronic battery comprising the nonlinear fluorinated copolymer of claim 1, an active material, a non-aqueous solvent and a conductive material and optionally a viscosity modifier.
18. The composition of claim 17, comprising: (a) a non-linear fluorinated copolymer in an amount of 0.5 to 5.0 wt. %, preferably 0.5 to 3.0 wt. %, relative to the total weight of (a) + (b) + (c); (b) a conductive material in an amount of 0.5 to 5.0 wt. %, preferably 0.5 to 3.0 wt. %, relative to the total weight of (a) + (b) + (c); (c) an active material, preferably a composite metal, in an amount of 90 to 99 wt. %, preferably 94 to 99 wt. %.
19. An electrode for a lithium electronic battery obtained by applying the composition of claim 18 to a metal film and drying the coating.
20. A lithium electronic battery having the electrode according to claim 19.
21. An article comprising the non-linear fluorinated copolymer of any one of claims 1 to 4.
Citation Information
Cited By
Modified polyvinylidene fluoride binder and preparation method thereof
CN119684932A
